Analysis of Deixis on the Holy Koran Surah Al-Baqarah Verses 183-185 - Niro Arif Sas (Institute of Educational, Research, and Community Service)
Deixis is a linguistic phenomenon in which the interpretation of certain words or phrases depends on contextual information, such as the identity of the speaker and listener, time and place of the utterance, social relationships, and the structure of the discourse. It plays a crucial role in understanding meaning, especially in learning English as a foreign language, where contextual awareness is essential for comprehension. This research aims to analyze the types and frequency of deixis found in the Koran, specifically in Surah Al-Baqarah verses 183–185. The study employs a descriptive qualitative method, focusing on a detailed analysis of the verses to identify the deixis expressions used. The findings reveal that four types of deixis are present: personal deixis, temporal deixis, discourse deixis, and social deixis. A total of 62 deixis expressions were identified, consisting of 21 personal deixis, 4 temporal deixis, 27 discourse deixis, and 10 social deixis. Among these, discourse deixis is the most frequently used, indicating the importance of textual reference and coherence in the verses analyzed. This suggests that the Koranic discourse in these verses emphasizes the continuity and interconnectedness of messages through the use of discourse markers and referential expressions. The study contributes to a deeper understanding of how deixis operates in religious texts and offers valuable insights for language learners, translators, and scholars interested in the pragmatic and semantic aspects of sacred discourse. It also highlights the importance of contextual interpretation in grasping the intended meanings of divine communication.